Perbandingan Peningkatan Pengetahuan Ibu Tentang Pijat Bayi Setelah Mendapat Penyuluhan dan Pemutaran VCD di Kelurahan Widodomartani, Ngemplak, Sleman, Yogyakarta - Ayu Widya Ningsih; MTS Darmawan; Titik Kuntari (Faculty of Medicine, Universitas Islam Indonesia, 2011)
With the many benefits that can be obtained from the habit baby massage performed by the mother, it is necessary once baby massage is used as a habit. But this attitude has been influenced by knowledge of mothers on infant massage itself. Until now not known how the mother's level of knowledge in the area Widodomartani village, about the benefits of baby massage. The bjective of this research to obtain the comparative increase in maternalknowledge about infant massage after receiving counseling and VCD playback. This study is a descriptive research approach to the pre test and post test. This study found that the value of significance (p) is smaller then 0.05: On theextension of Ho rejected and Ha accepted means that there are significant differences between mother’s knowledge level of infant massage before and after extension. On playback VCD Ho rejected and Ha accepted. This means that there are significant differences between mother’s knowledge about infant massage before and after the VCD playback. On increasing knowledge is rejected and Ho Ha received. This means there is no significant differencebetween the increase in maternal knowledge about infant massage compared with VCD playback with increased knowledge counseling.This study conclude that there were significant differences between the mother’s knowledgeabout infant massage before and after counseling.There were significant differences between the mother’s knowledge about infant massage before and after VCD playback. There were no significant differences between theincrease of mother’s knowledge after VCD playback and counseling method.Key Words: Knowledge, Infant Massage, VCD, counseling, Widodomartani